CLIFF-GRADS Science Collaboration Series 2020 -Thematic student session: Pasture & Agronomy Systems - Arango, Jacobo; Maguire, Vanina Giselle; Gnavo, Pénéloppe Thertulienne; Alecrim, Fabiano; Gebreslase, Shimbahri Mesfin; Ramalho, Israel Oliveira (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Featured Speaker: Dr. Jacobo Arango, Environmental Biologist at the Tropical Forages Program at CIAT.